Extracellular space structure revealed by diffusion analysis - Nicholson, Charles; Syková, Eva (Trends in neurosciences, 1998)
The structure of brain extracellular space resembles foam. Diffusing molecules execute random movements that cause their collision with membranes and affect their concentration distribution. By measuring this distribution, the volume fraction (alpha) and the tortuosity (lambda) can be estimated. The volume fraction indicates the relative amount of extracellular space and tortuosity is a measure of hindrance of cellular obstructions. Diffusion measurements with molecules <500 Mr show that alpha approximately 0.2 and lambda approximately 1.6, although some brain regions are anisotropic. Molecules > or =3000 Mr show more hindrance, but molecules of 70000 Mr can move through the extracellular space. During stimulation, and in pathophysiological states, alpha and lambda change, for example in severe ischemia alpha = 0.04 and lambda = 2.2. These data support the feasibility of extrasynaptic or volume transmission in the extracellular space.
Keywords: Animals; mozková kůra; extracelulární prostor; corpus callosum; Brain Injuries; lidé; Cerebral Cortex; Diffusion; zvířata; Humans; poranění mozku; difuze; Brain; mozek; Extracellular Space; Corpus Callosum